FORMATION AND DEVELOPMENT OF MOBILE COMMUNICATION TERMINOLOGY (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The rapid advancement of mobile communication has led to the formation and continuous evolution of specialized terminology. This article explores the development of mobile communication terminology. The study examines linguistic processes such as borrowing, compounding, abbreviation, and semantic shift. Findings suggest that globalization, technological innovation, and digital culture contribute significantly to the expansion and adaptation of mobile communication terminology. The paper also discusses how mobile terminology influences communication across different languages and cultures.